Collective Memory and National Identity Formation: The Role of Family and the State - Björn Brey; Joanne Haddad; Lamis Kattan (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
State-led repression of minority identities is a well-documented phenomenon, yet its implications for national identity remain understudied. We examine how the Soviet state-induced famine (1932–33) shapes contemporary Ukrainian national identity through vertical (familial) and horizontal (community/state) transmission. Using newly geocoded individual-level data, we find that individuals from high-famine-exposure areas are more likely to identify as Ukrainian. We document that under Soviet rule, family networks preserved identity, while church closures weakened community transmission. After independence, state-led remembrance efforts, revitalized horizontal transmission. Our findings show how repression and remembrance shape identity persistence and reflect the famine's lasting influence on Ukrainian-Russian relations.
Keywords: D74; N44; P20; P35; Z13; 330; political repression; national identity; intergenerational transmission; historical memory; trade; conflict